Bimetal chloride catalyzed hydrogenation of silicon tetrachloride in the presence of silicon. (23rd December 2022) - Ji, Yuwen; Wang, Huhu; Jia, Zhaohang; Peng, Wencai; Zhang, Jinli; Zhang, Jianshu
Abstract : Due to the better dispersion and formation of more copper silicides, the catalytic performance of bimetallic chlorides was significantly improved. Abstract : The efficient conversion of the by-product SiCl4 to SiHCl3 remains a huge challenge for the Siemens process, the most popular polysilicon manufacturing process. Herein, hydrogenation of SiCl4 in the presence of Si was investigated in a fixed-bed reactor over various transition metal chlorides and bimetal chloride catalysts. Catalytic performances of bimetal chloride were increased significantly compared to those of monometallic chloride catalysts. The conversion of SiCl4 for Cu 10%–Ni 10% and Cu 10%–Co 10% reached 19.68% and 20.96% at 500 °C, respectively, when the molar ratio of H2 /SiCl4 was 4 : 1 and the H2 volume flow was 200 mL min −1 . Bimetal chloride catalysts showed an obvious synergistic effect during the catalytic process. Metal chloride precursors would be transformed into the corresponding metal silicides as active phases via a solid–solid reaction. As for bimetal chloride catalysts, the presence of Co or Ni was beneficial to the dispersion of metals and the reduction of Cu. And it was favorable to the formation of more copper silicides, which is responsible for the excellent catalytic performance of bimetal chloride catalysts.